2014
DOI: 10.1039/c4ob00618f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized chromones through sequential reactions in aqueous media

Abstract: An efficient sequential four-component reaction of chromone carbaldehydes, Meldrum's acid, 4-hydroxyl coumarin or 6-methyl-4-hydroxyl-pyrone and primary alcohols is reported which leads to 5a-i in aqueous media. Replacing the primary alcohol with isopropyl alcohol and tert-butyl alcohol results in different products 10 and 11. The environmentally friendly features, good to high yields and easy work-up are advantages of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…185 Replacing the primary alcohol with isopropyl and tert-butyl alcohol results in the cyclized product, chromenyl-dihydropyrano[3,2-c]chromene 263, or functionalized carboxylic acid 264, respectively. The proposed mechanism involves an initial Knoevenagel reaction of 3-formyl chromone 259 and Meldrum's acid 260, followed by a Michael addition of the deprotonated form of 4-hydroxycoumarin 26 to the alkylidene of Meldrum's acid.…”
Section: Synthesis Of Coumarin-linked and Coumarin-fused Heterocyclesmentioning
confidence: 99%
“…185 Replacing the primary alcohol with isopropyl and tert-butyl alcohol results in the cyclized product, chromenyl-dihydropyrano[3,2-c]chromene 263, or functionalized carboxylic acid 264, respectively. The proposed mechanism involves an initial Knoevenagel reaction of 3-formyl chromone 259 and Meldrum's acid 260, followed by a Michael addition of the deprotonated form of 4-hydroxycoumarin 26 to the alkylidene of Meldrum's acid.…”
Section: Synthesis Of Coumarin-linked and Coumarin-fused Heterocyclesmentioning
confidence: 99%
“…168 Fluoro-and iodo-substituted derivatives 164 exhibited the highest antimicrobial (P. aeruginosa and S. aureus), antiprotozoal (E. histolytica), and antifungal (Sporothrix schenckii, C. albicans, and Candida tropicalis) activities. 169 Mehrparvar et al 170 demonstrated the possibility to introduce the carbonyl group into the (chromonyl)hetarylmethane core. The successive treatment of 3-formylchromones 1 with Meldrum's acid, 4-hydroxycoumarin (10) or 4-hydroxy-6-methylpyran-2-one (11) in aqueous primary alcohol gave esters 165.…”
Section: Synthesis Of Heterocyclic Analogs Of Homoisofl Avonoidsmentioning
confidence: 99%
“…In continuation of our research work [54][55][56][57][58][59][60][61][62][63][64], we report herein the synthesis of quinazolinone sulfonamides through the four-component reaction of isatoic anhydride, hydrazine hydrate, benzaldehyde derivatives, and saccharin under solvent-free conditions using propylsulfonic acid …”
Section: Introductionmentioning
confidence: 99%